1990
DOI: 10.1093/bja/64.5.590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Midazolam on Median Nerve Somatosensory Evoked Potentials

Abstract: We have studied the effect of i.v. midazolam on median nerve somatosensory evoked potentials (SSEP) in 10 unpremedicated adults. Anaesthesia was induced with midazolam by bolus administration (0.2 mg kg-1) followed by infusion (5 mg h-1). The latency and amplitudes of the SSEP responses over the second cervical vertebrae (SC2) and sensory cortex (P17, N20, P25) were recorded before and for 10 min after induction. Data were analysed over that period for time-related alterations. Small but statistically signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…[18][19][20]25 The influence of midazolam used for premedication can be neglected, as several studies showed no or only a transient effect on SSEP latencies. 22,26,27 Also the application of low doses of opioids (fentanyl) is not supposed to induce the predictable changes on SSEP latencies. 18,22,28 The intraoperative within-case variability of SSEP is of relevance in performing neuromonitoring during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20]25 The influence of midazolam used for premedication can be neglected, as several studies showed no or only a transient effect on SSEP latencies. 22,26,27 Also the application of low doses of opioids (fentanyl) is not supposed to induce the predictable changes on SSEP latencies. 18,22,28 The intraoperative within-case variability of SSEP is of relevance in performing neuromonitoring during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Is-21 In addition, latencies of subcortical and cortical responses of the somatosensory evoked potentials (SSEP) remain unchanged with benzodiazepines. [20][21][22][23][24] demonstrated that midazolam produced a depression of cortical SSEP amplitude without alterations in latency. 24 In contrast to the benzodiazepines, the influence of general anaesthesia on MLAEP has been well studied for the volatile anaesthetic agents isoflurane, enflurane and halothane, so.,I With volatile anaesthetics, brainstem components of the auditory evoked potential are only slightly prolonged in latency.…”
Section: Discussionmentioning
confidence: 99%
“…However, in daily clinical practice, neurological examination will be performed after wearing off of sedative drugs and before requesting a SEP. Furthermore, sedative drugs such as propofol or midazolam only seem to cause marginal effects on latency and amplitude of the cortical N20 responses [2628]. …”
Section: Discussionmentioning
confidence: 99%